2010
DOI: 10.1021/jp9112766
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Pulsed Laser Deposition of Nanostructured CdS Films

Abstract: In this work we report an investigation of the properties of nanostructured deposits obtained from femtosecond pulsed laser deposition of CdS sintered targets. Specifically, we address the effect of laser irradiation wavelength, laser fluence and substrate temperature (from 25 to 450 ºC). The composition of the deposits was characterized using X-ray photoelectron spectroscopy (XPS), their crystallinity by Xray diffraction (XRD) and the surface morphology was studied by environmental scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 29 publications
(70 reference statements)
3
29
0
Order By: Relevance
“…However, it can be noted that since the ns pulse is much longer than the electron-phonon relaxation time, which determines the time for heat conduction in the fs case, the heat diffusion depth is smaller in the fs case. In fs ablation most of the ablated material is removed by nanofragmentation of superheated material, 15,17,34,35 while in the ns ablation material removal is limited by surface evaporation from the laser heated surface. In ns ablation plume material evolved during the laser pulse absorbs the laser light leading to a reduction of the energy coupled to the target.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it can be noted that since the ns pulse is much longer than the electron-phonon relaxation time, which determines the time for heat conduction in the fs case, the heat diffusion depth is smaller in the fs case. In fs ablation most of the ablated material is removed by nanofragmentation of superheated material, 15,17,34,35 while in the ns ablation material removal is limited by surface evaporation from the laser heated surface. In ns ablation plume material evolved during the laser pulse absorbs the laser light leading to a reduction of the energy coupled to the target.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it is known that in fs irradiation a significant part of the ablation occurs via emission of nanoparticles (NPs), which leave the target at lower velocity than atoms or ions and emit a continuous light spectrum. [15][16][17] There are some reports of ion energy distribution measurements using Langmuir probes 7 or ion energy analyzers, 2,4,7,11 but these measurements have been made in a direction close to the normal of the target surface, and do not give information about the shape of the ablation plume. Donnelly et al 8,9 have used ion probes to measure the plume shape and the ion energy distribution in fs ablation of nickel.…”
Section: Introductionmentioning
confidence: 99%
“…1993, Sanz et al 2011). Previous studies on the influence of deposition conditions on the characteristics of CdS and ZnS deposits grown by PLD using fs pulses (Tong et al 2008, Sanz et al 2010 have revealed a significant influence of laser wavelength and substrate temperature on the properties of the deposits.…”
Section: Introductionmentioning
confidence: 98%
“…When performed in vacuum or gas environment, it is typically used for growing thin solid films or nanostructured materials like nanoparticles (NPs) of multiple elements, from polymers and biomaterials to oxides, carbides, nitrides, or metals [1][2][3][4][5][6][7][8][9][10][11]. When applied in a liquid environment, fs-PLA allows the synthesis of colloidal solutions of NPs from the ablated material in a complex process that involves: (i) the absorption of the laser pulse by multiphoton absorption and direct photoionization; (ii) the ablation or fragmentation of the bulk material in the form of hot atoms, vapors, and liquid drops under non-equilibrium conditions; (iii) the expansion and quenching of the plasma plume; (iv) the expansion and collapse of the cavitation bubble; and (v) the growth and agglomeration of the NPs.…”
Section: Introductionmentioning
confidence: 99%